Isolation and identification of denitryifing from indegenous mircroorganism - Maizatul Farhain, Ismail; Nurul 'Azyyati, Sabri; Saiful Nizam, Tajuddin; Lee, Chin Mei; Siti Hatijah, Mortan; Ab. Rahim, Mohd-Hairul (The Official Publication of The Malaysian Society for Biochemistry & Molecular Biology (MSBMB), 2019)
The objective of this study was to isolate and identify novel potential denitrifying bacteria from two different Kuantan areas which are Jubli Perak Agricultural Park, Kuantan (3º50'49.6"N103º18'06.1"E) and Felda Lepar Hilir, Kuantan (3º40'41.4"N 103º03'24.7"E). Indigenous Microorganisms (IMOs) available in the locations were cultivated by fermentation of steamed rice in the location together with brown sugar. Serial dilutions of the fermented medium were spread on Jensen’s agar and incubated at 30 ºC for eight days. A total of six colonies were subjected to various biochemical analysis including Gram staining, catalase, methyl red, carbohydrate fermentation and nitrate reduction tests. All bacterial isolates were subjected to genomic DNA extraction and PCR amplification of 16S rRNA genes using 27F and 1942R primers. All the amplified product of 16S rRNA genes from the bacterial isolates were purified and sent for sequencing. BLASTn and phylogenetic analysis based on 16S rRNA gene sequences shown all the isolates belong to Bacillus spp. and clustered into two main clusters.